Działalność publiczna Tęczyńskich w XVII wieku. Kariery Gabriela (zm. 1617), wojewody lubelskiego i Andrzeja (zm. 1613), kasztelana bełskiego - Pielas, Jacek (Saeculum Christianum. Pismo Historyczne, 2020)
The article presents the careers of two representatives of one of the oldest Polish magnate families – Tęczyński, coat of arms Topór, the elder sons of Andrzej (d. 1588), the governor of Krakow: Gabriel (d. 1617), the voivode of Lublin and Andrzej (d. 1613), the castellan of Bełz, living at the turn of the 16th and 17th centuries. It has been proven that after a long period of education outside the borders of the Commonwealth, which was interrupted in 1593 by an episode, when the brothers were sent to the General Sejm, from the beginning of the 17th century, as young magnate sons, they actively participated in the public life. Gabriel worked in the local government of the Lublin Voivodeship, while Andrzej was a member of the Opatów regional parliament. Although the brothers did not reach the highest state offices – the end of Gabriel's career was Lublin voivodship, and Andrzej castellany of Bełz – they showed significant activity during the Sandomierz rebellion in 1606-1607, taking the side of the royal camp. In the following years, Andrzej Tęczyński expressed his support for the royal party in his views and attitude, while the elder Gabriel distanced himself from the policy of Sigismund III Vasa at least from 1611. Their careers ended with fairly sudden deaths, after which the public activity was taken up by the youngest of their brothers - Jan Magnus (d. 1637), the voivode of Kraków, with whom the Tęczyński line came to an end.